THE DEVELOPMENT OF DIDACTICAL DESIGN ON THE TOPIC OF ABSOLUTE VALUE TO BUILD STUDENTS' STRATEGIC COMPETENCE, ADAPTIVE REASONING, AND PRODUCTIVE DISPOSITION - Herdian, Ade (2016)
This research is a didactical design research (DDR) aimed to obtain an ideal learning design on the topic of absolute value to build students' mathematical proficiencies particularly strategic competence, adaptive reasoning and productive disposition. The research was conducted to solve problem of teaching and learning absolute value that has created learning obstacles on students. Using the three phases of DDR, the study put concern on (1) the process of developing didactical design based on the analysis towards arising learning obstacles, (2) the process of implementing the didactical design and the DPA (Didactical and Pedagogical Anticipation) and (3) the process of evaluating the implementation of the design. The techniques of data gathering used in this research are tests, direct observation, tasks, interviews and questionnaire. The obtained data then are analyzed using descriptive exploratory method to get rich and detailed information about the data. The process of developing didactical design has produced a didactical design on the topic of absolute value in three learning designs for three meetings including the DPA for each design. The implementation of the developed design has shown that the process of constructive learning happened effectively. The students' work on group discussion during the learning process and on individual test given after the learning sessions have finished, have shown the development of the expected mathematical proficiencies by the percentage of achievement respectively 80.15% and 50.19%. The questionnaire given to the students also has shown positive responses confirming the development of their productive disposition.;--- Penelitian ini adalah penelitian desain didaktis (DDR) yang bertujuan untuk mendapatkan desain pembelajaran yang ideal pada topik nilai mutlak untuk membangun kecakapan matematik siswa khususnya kompetensi strategis, penalaran adaptif dan disposisi produktif. Penelitian ini dilakukan untuk menemukan solusi atas permasalahan pembelajaran nilai mutlak yang telah memberikan hambatan-hambatan belajar pada siswa. Dengan menggunakan tiga tahapan DDR, penelitian ini memfokuskan kajian pada (1) proses pengembangan desain didaktis berdasarkan analisis terhadap hambatan-hambatan belajar yang muncul, (2) proses implementasi desain didaktis yang sudah dikembangkan termasuk ADP (Antisipasi Didaktis dan Pedagogis) dan (3) proses evaluasi terhadap implementasi dari desain didaktis. Teknik pengumpulan data yang digunakan dalam penelitian ini antara lain adalah tes, observasi langsung, tugas kelompok, wawancara dan kuesioner. Data yang diperoleh selanjutnya dianalisa secara deskriptif eksploratori untuk mendapatkan informasi yang lengkap dan detail mengenai data tersebut. Proses pengembangan desain didaktis telah menghasilkan suatu desain didaktis pada topik nilai mutlak dalam tiga bahan ajar untuk tiga pertemuan termasuk ADP untuk masing-masing bahan ajar tersebut. Implementasi dari desain bahan ajar yang sudah dikembangkan tersebut memperlihatkan bahwa proses pembelajaran konstruktif telah terselenggara secara efektif. Hasil kerja siswa dalam diskusi kelompok selama proses pembelajaran serta hasil kerja mereka pada tes individual pasca pembelajaran telah menunjukkan perkembangan kecakapan matematik mereka dengan persentasi tingkat pencapaian berturut-turut 80.15% dan 50.19%. Kuesioner yang diberikan kepada siswa juga menunjukkan respon-respon positif yang menguatkan perkembangan dari kecakapan disposisi produktif mereka.